The Charming World of the Extracellular Matrix: A Dynamic and Protective Network of the Intestinal Wall - Pompili, Simona; Latella, Giovanni; Gaudio, Eugenio; Sferra, Roberta; Vetuschi, Antonella (Frontiers in Medicine, 2021)
The intestinal extracellular matrix (ECM) represents a complex network of proteins that not only forms a support structure for resident cells but also interacts closely with them by modulating their phenotypes and functions. More than 300 molecules have been identified, each of them with unique biochemical properties and exclusive biological functions. ECM components not only provide a scaffold for the tissue but also afford tensile strength and limit overstretch of the organ. The ECM holds water, ensures suitable hydration of the tissue, and participates in a selective barrier to the external environment. ECM-to-cells interaction is crucial for morphogenesis and cell differentiation, proliferation, and apoptosis. The ECM is a dynamic and multifunctional structure. The ECM is constantly renewed and remodeled by coordinated action among ECM-producing cells, degrading enzymes, and their specific inhibitors. During this process, several growth factors are released in the ECM, and they, in turn, modulate the deposition of new ECM. In this review, we describe the main components and functions of intestinal ECM and we discuss their role in maintaining the structure and function of the intestinal barrier. Achieving complete knowledge of the ECM world is an important goal to understand the mechanisms leading to the onset and the progression of several intestinal diseases related to alterations in ECM remodeling.